2017
DOI: 10.1002/adma.201702931
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Edge Contact: Atomically Resolved Semiconductor–Metal Lateral Boundary in MoS2

Abstract: Despite recent efforts for the development of transition-metal-dichalcogenide-based high-performance thin-film transistors, device performance has not improved much, mainly because of the high contact resistance at the interface between the 2D semiconductor and the metal electrode. Edge contact has been proposed for the fabrication of a high-quality electrical contact; however, the complete electronic properties for the contact resistance have not been elucidated in detail. Using the scanning tunneling microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In particular, VFETs with van der Waals heterostructures (vdWHs) comprising graphene electrodes, multilayer TMD channels, and metal electrodes have garnered considerable attention because of the high ON current densities for low-power consumption and high-speed as well as the high scalability in limited-circuit areas. [12][13][14][15] In multilayers TMD FETs, at vdW interfaces such as the electrode/TMD and TMD interlayer interfaces, the Schottky barrier and electrostatic potential barriers form highinterface resistances which reduce the injected carrier transport efficiency significantly [16][17][18][19] (Figure 1a,b). Therefore, these resistances at vdW interfaces are critical obstacles preventing the development of high-speed and low-power multilayer TMD material FETs regardless of the structure type of FETs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, VFETs with van der Waals heterostructures (vdWHs) comprising graphene electrodes, multilayer TMD channels, and metal electrodes have garnered considerable attention because of the high ON current densities for low-power consumption and high-speed as well as the high scalability in limited-circuit areas. [12][13][14][15] In multilayers TMD FETs, at vdW interfaces such as the electrode/TMD and TMD interlayer interfaces, the Schottky barrier and electrostatic potential barriers form highinterface resistances which reduce the injected carrier transport efficiency significantly [16][17][18][19] (Figure 1a,b). Therefore, these resistances at vdW interfaces are critical obstacles preventing the development of high-speed and low-power multilayer TMD material FETs regardless of the structure type of FETs.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) group-VIB transition metal dichalcogenides (TMDs) have generated considerable research interest in recent years for both fundamental studies and application prospects as a result of their inherent energy gaps and numerous other promising features such as the transformation from the indirect to direct bandgap when approaching the monolayer limit. [1][2][3][4][5][6][7][8][9] In particular, semiconducting TMDs with the general expression of MX2 (M represents Mo or W and X symbolizes S or Se) 6,10 are considered interesting candidates for achieving valleytronics, 11,12 one rather interesting field where valley degree of freedom is explored as an information carrier. 13 In monolayer TMDs, there exist inequivalent and energetically degenerate valleys at K and K' points in the hexagonal Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum disulfide (MoS 2 ) has attracted considerable attention because of its excellent properties and potential applications in electrocatalysis, energy storage, , and electronic devices. , Metallic 1T-phase MoS 2 shows superior performance in several applications, including hydrogen evolution reaction (HER) catalysts, actuators, supercapacitors, and edge contact transistors, , due to its abundant active sites and excellent electrical conductivity. Unfortunately, the 1T-phase MoS 2 synthesized by traditional approaches including chemical exfoliation, hot electron injection, electron beam irradiation, 14 and metallic atom doping ,, is metastable and tends to devolve back into the 2H phase. The unstable nature of the 1T phase is attributed to its substantially higher energy relative to that of the 2H phase, thus resulting in transformation of the metastable 1T structure to a thermally preferred 2H phase, even under aging in air. , As a result, the preparation of ultrastable 1T-MoS 2 for practical applications remains a substantial challenge. Previous works showed that both mechanical strain and an electrostatic field could induce the 1T phase transition. ,, The mechanical strain method developed by Zheng’s group required a periodic gold cone substrate to induce the strain .…”
mentioning
confidence: 99%